Implementing animation production process: case study of Desktop Application Learning System (MiLO) for front office management / Hafizah Rosli...[et al.] - Rosli, Hafizah; Woo, Pak Yuan; Mohd Shahril, Aslinda; Azmi, Ezwani; Mohd Akhir, Irina (Universiti Teknologi MARA, Kedah, 2020)
The rise of learning innovation suggested that distance learning included the use of technologies such as video, audio, computer and multimedia communications into supporting extended teaching and learning tools. However, despite an increasing number of learning innovation, there has been little detailed documentation of the processes involved in this format of animation production process. More specifically, there has been little documentation and analysis of the key considerations and issues that might confront practitioners when integrating 3D animation production process with teaching and learning tool. This paper aims to examine the 3D animation production process of Desktop Application Learning System: Multimedia Interactive Learning Online (MiLO) by Kemmis & McTaggart Action Research Model. Qualitative research applied by action research methodologies and make use of reflective practice across a series of action research cycles in the form of making the 3D animation for the desktop learning application. The findings of this paper propose a new framework of animation production process for teaching and learning application by using iClone software. This paper contribution a new framework of animation production process for teaching and learning application for future researcher or designer to use it on another field that feeds the grounds.